A Randomized Controlled Trial Comparing Carbetocin and Oxytocin for the Prevention of Postpartum Hemorrhage in Elective and Emergency Cesarean Deliveries - Dr. P. G. Raghavendra, Dr. Sahana P R (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Postpartum hemorrhage(PPH) remains a leading cause of maternalmorbidity worldwide. Oxytocin is thetraditional first-line uterotonic, whereasCarbetocin, a longer-acting analogue, may offer superior uterine tone and reduced need for additional interventions.